SMOKING BEHAVIOR AMONG STUDENTS AND ITS MANAGEMENT : CASE STUDY OF TWO STUDENTS AT THE STATE SPF 8 MAKASSAR UPT - Rosita, Sitti; Pandang, Abdullah; Saman, Abdul (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze smoking behavior among students at UPT SPF SMP Negeri 8 Makassar and the efforts to address it. The method used is a qualitative approach with a case study design, involving two subjects, namely students with the initials DP and RPS, who have been identified as having smoking behavior. Data were collected through interviews and observations, and analyzed descriptively using triangulation techniques. The results of the study indicate that the smoking behavior of both students is perceived as normal and enjoyable, with consumption reaching one pack per day. Factors influencing this behavior include the desire for recognition, peer influence, and imitation from parents. The handling of smoking behavior was conducted through cognitive restructuring techniques consisting of six stages: rationalization, identification of thoughts, introduction and training of coping thoughts, shifting negative thoughts, positive reinforcement exercises, and evaluation. After the intervention, there was a change in thinking from irrational to rational, which is expected to reduce students' smoking behavior.